VIOLA MCBEE’S DISLOCATED BELONGING: BLACK WOMANHOOD AND RACIAL VIOLENCE IN ARNOLD EDWARDS’ COME FULL CIRCLE - Faqih, Achmad; Zahroh, Fatimatuz; Taufik, Moh.; Utami, Yuni Putri; Linia, Marisa; Fane, Awati (Pengkajian Amerika, Universitas Gadjah Mada, 2026)
This article investigates how Black womanhood and racial violence are portrayed in Arnold Edwards’s Come Full Circle through the character of Viola McBee, a Black woman whose life is shaped by unresolved trauma, historical injustice, and spatial displacement. The research is motivated by the need to understand how literature represents the intersections of race, gender, and memory, particularly in narratives centered on Black women’s lived experiences. The central problem concerns how dislocated belonging operates in Viola’s identity as both victim and agent of justice. Drawing on Critical Race Feminism, Black Feminist Thought, and Spatial Theory, the study employs a qualitative textual analysis to examine how Viola’s response to racial and sexual violence challenges legal justice and redefines moral accountability. The findings reveal that Viola resists dominant cultural narratives that demand silence or forgiveness, asserting her agency by transforming personal memory into political resistance. Her character challenges the spatial and legal structures that exclude Black women, making visible the emotional and material costs of systemic violence. The article contributes to American Studies by demonstrating how fictional texts can confront historical silences and center Black women’s voices as vital frameworks for ethical and political critique.